Opposing roles of CB1 and CB2 cannabinoid receptors in the stimulant and rewarding effects of cocaine. (14th September 2018) - Gobira, Pedro H; Oliveira, Ana C; Gomes, Julia S; da Silveira, Vivian T; Asth, Laila; Bastos, Juliana R; Batista, Edleusa M; Issy, Ana C; Okine, Bright N; de Oliveira, Antonio C; Ribeiro, Fabiola M; Del Bel, Elaine A; et al.
Abstract : Background and Purpose: The endocannabinoids anandamide and 2‐arachidonoylglycerol (2‐AG) bind to CB1 and CB2 cannabinoid receptors in the brain and modulate the mesolimbic dopaminergic pathway. This neurocircuitry is engaged by psychostimulant drugs, including cocaine. Although CB1 receptor antagonism and CB2 receptor activation are known to inhibit certain effects of cocaine, they have been investigated separately. Here, we tested the hypothesis that there is a reciprocal interaction between CB1 receptor blockade and CB2 receptor activation in modulating behavioural responses to cocaine. Experimental Approach: Male Swiss mice received i.p. injections of cannabinoid‐related drugs followed by cocaine, and were then tested for cocaine‐induced hyperlocomotion, c‐Fos expression in the nucleus accumbens and conditioned place preference. Levels of endocannabinoids after cocaine injections were also analysed. Key Results: The CB1 receptor antagonist, rimonabant, and the CB2 receptor agonist, JWH133, prevented cocaine‐induced hyperlocomotion. The same results were obtained by combining sub‐effective doses of both compounds. The CB2 receptor antagonist, AM630, reversed the inhibitory effects of rimonabant in cocaine‐induced hyperlocomotion and c‐Fos expression in the nucleus accumbens. Selective inhibitors of anandamide and 2‐AG hydrolysis (URB597 and JZL184, respectively) failed to modify this response. However, JZL184 prevented cocaine‐induced hyperlocomotion when given after a sub‐effective dose of rimonabant. Cocaine did not change brain endocannabinoid levels. Finally, CB2 receptor blockade reversed the inhibitory effect of rimonabant in the acquisition of cocaine‐induced conditioned place preference. Conclusion and Implications: The present data support the hypothesis that CB1 and CB2 receptors work in concert with opposing functions to modulate certain addiction‐related effects of cocaine. Linked Articles: This article is part of a themed section on 8 th European Workshop on Cannabinoid Research. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.10/issuetoc